The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2004
DOI: 10.1103/physreve.69.056610
|View full text |Cite
|
Sign up to set email alerts
|

Rolling and slipping motion of Euler’s disk

Abstract: We present an experimental study of the motion of a circular disk spun onto a table. With the help of a high speed video system, the temporal evolutions of (i) the inclination angle α, (ii) the angular velocity ω and (iii) the precession rate Ω are studied. The influence of the mass of the disk and the friction between the disk and the supporting surface are considered. The inclination angle α and the angular velocity are observed to decrease according to a power law. We also show that the precession rate Ω di… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

6
31
0
3

Year Published

2008
2008
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 37 publications
(40 citation statements)
references
References 8 publications
6
31
0
3
Order By: Relevance
“…The experimental results agree with values of n between 1 2 and 2 3 . Measurements on a torus are believed in [5] to confirm the supposition of van den Engh et al [23] that air drag is only of minor importance.…”
Section: Introductionsupporting
confidence: 66%
See 2 more Smart Citations
“…The experimental results agree with values of n between 1 2 and 2 3 . Measurements on a torus are believed in [5] to confirm the supposition of van den Engh et al [23] that air drag is only of minor importance.…”
Section: Introductionsupporting
confidence: 66%
“…Caps et al [5] present a rather detailed experimental study of various rolling disks using a high-speed video camera (125-500 fps) and a laser beam during about 10 s. The inclination angle, precession rate and angular velocity around the axis of symmetry of the disk are each measured with a different experimental setup during a different run and, therefore, have not been obtained simultaneously. The experimental results agree with values of n between 1 2 and 2 3 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Since then, results on the dynamics of a rigid body have been reported in a tremendous body of literature [2][3][4][5]. Owing to Moffatt's recent work [6], this classical problem has recently revived interest for studying the energy dissipation in the motion of a 'Euler's disc', namely a circular (homogeneous) metal disc spinning on a flat surface [7][8][9][10][11][12][13][14]. In this system, while its mechanical energy is dissipating, paradoxically, the speed of the disc's rolling increases rapidly.…”
Section: Introductionmentioning
confidence: 99%
“…Easwar et al [9] reported an exponent n = 3 through experiments using a single high-speed camera to measure the precession rate. Caps [8] performed a series of experiments to separately measure the inclination angle, precession rate and angular velocity around the symmetric axis of the disc, and presented the exponent with a value varying between n = 3 and 4. Leine [10] adopted a high-speed camera to synchronically measure the inclination angle and the precession rate, and suggested that the exponent is either n = 4 or 3.…”
Section: Introductionmentioning
confidence: 99%